2003
DOI: 10.1103/physrevlett.90.068302
|View full text |Cite
|
Sign up to set email alerts
|

Surface Dynamics of Polymer Films

Abstract: The dynamics of supported polymer films were studied by probing the surface height fluctuations as a function of lateral length scale using x-ray photon correlation spectroscopy. Measurements were performed on polystyrene (PS) films of thicknesses varying from 84 to 333 nm at temperatures above the PS glass transition temperature. Within a range of wave vectors spanning 10(-3) to 10(-2) nm(-1), good agreement is found between the measured surface dynamics and the theory of overdamped thermal capillary waves on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
205
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(224 citation statements)
references
References 19 publications
11
205
0
Order By: Relevance
“…A couple of the remarkable studies will be reviewed here. The overdamped capillary waves of polystyrene films are observed by Kim et al 60) and Jiang et al, 61,62) and they discussed the relation between the mobility of the polymer chains and the thickness of the film. Madsen et al observed the dispersion relation of the capillary waves on liquid surface near the transition point from oscillating to overdamped behavior.…”
Section: X-ray Photon Correlation Spectroscopymentioning
confidence: 92%
See 1 more Smart Citation
“…A couple of the remarkable studies will be reviewed here. The overdamped capillary waves of polystyrene films are observed by Kim et al 60) and Jiang et al, 61,62) and they discussed the relation between the mobility of the polymer chains and the thickness of the film. Madsen et al observed the dispersion relation of the capillary waves on liquid surface near the transition point from oscillating to overdamped behavior.…”
Section: X-ray Photon Correlation Spectroscopymentioning
confidence: 92%
“…Surface tension, one of the most important physical properties of surface, is predicted to have spatial scale dependence (q dependence) in microscopic scale due to the atomic or molecular effect by the density functional theory for capillary wave fluctuations. 68,69) XPCS today can access up to q $ 5 Â 10 À2 nm À1 and down to t $ 10 0 s for capillary waves of polystyrene films 60) and the behavior can be described by macroscopic fluid mechanics. Damping rate of capillary waves in microscopic region q $ 1 nm À1 is estimated faster than t $ 10 À4 s by conventional fluid mechanics.…”
Section: Perspective Of Xpcsmentioning
confidence: 99%
“…Further, assuming validity of Stokes-Einstein (SE) relation, which is expected to hold at measurement temperatures which are ∼ 50-60 K above T g , as has been shown earlier for thin polymer films, 33 we can write τ ∼…”
Section: (A)-2(b))mentioning
confidence: 99%
“…This requires a preliminary knowledge of the fluid viscosity, which can be obtained by applying the same method with a different geometry. Actually, levelling has already been used to measure viscosity [13,14], assuming no slip at the fluid-solid interface and referring to the analytical solution for free-surface profiles with infinitesimal amplitudes, but without an evaluation of the approximations involved. This point is analysed here.…”
Section: Introductionmentioning
confidence: 99%